Implementation of Bos Fund Management To Maximize Learning Quality At Sdn 23 Talang Kelapa Banyuasin - Edi Yanto; Tri Widyatsih; Djunaidi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aims to analyze the implementation of School Operational Assistance (BOS) Fund management in improving learning quality at SDN 23 Talang Kelapa Banyuasin. A descriptive qualitative approach was employed involving four informants, namely the principal, BOS treasurer, teacher, and school committee representative. Data were collected through observation, semi-structured interviews, and documentation and analyzed using the interactive model of Miles and Huberman. The findings reveal that BOS Fund management has been implemented systematically through participatory planning, transparent implementation, accountable financial reporting, and collaborative supervision. Supporting factors include strong principal leadership, stakeholder collaboration, and compliance with technical guidelines, while limited budgets, administrative workload, and delays in fund disbursement remain major challenges. Although BOS Funds have improved learning facilities and classroom quality, greater investment in technology-based learning and teacher professional development is still required. This study contributes to educational management by providing empirical evidence that transparent and participatory financial management enhances learning quality and school governance at the elementary education level.